Remediation of aqueous solution of cypermethrin and chlorpyriphos using derived adsorbent from Jatropha curcas - F.O. Okeola; E.O. Odebunmi; F.O. Nwosu; T.O. Abu; O.S. Idiagbonya; M.A. Amoloye; F.T. Onifade; A.G. Abdulmummeen (Journal of Applied Sciences and Environmental Management, 2017)
The study focused on assessment of removal of cypermethrin and chloropyriphos in aqueous solution using activated carbon made from Jatropha Curcas. Batch adsorption experiments were carried out under different conditions of parameters such as pH, contact time, adsorbent dosage, and initial concentration of the adsorbate on pesticide adsorption. The adsorption data were described by Langmuir and Freundlich adsorption model. Adsorption capacity of 92.73% and 92.26% of chloropyriphos and cypermetrin respectively were removed by 2g of the adsorbent per 50 cm3 of initial concentration of 0.78 mg/l and 1.50 mg/l chloropyriphos and cypermetrin respectively .This was achieved at 90 min of the contact time and at optimum pH of 6.3.The study demonstrates that the activated carbon made from Jatropha Curcas can be effective in the adsorption of these two pesticides from water bodies. Equilibrium experiment results show that adsorption isotherms of cypermethrin and fit better to Freundlich adsorption isotherm while chloropyriphos fit better on the Langmuir adsorption isotherm.